Carleson measures on Hardy spaces with bicomplex scalars - Dolkar, Stanzin; Kumar, Sanjay (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.53We explore Carleson measures given on the Hardy spaces defined over the bicomplex space and investigate the properties of the bicomplex Toeplitz operator. In the first section, we provide a comprehensive introduction and formulate the key definitions necessary for the subsequent analysis. In the second section, we present the results for $\mathbb{D}$-Carleson measures and establish their relationship with bicomplex Hardy spaces. Finally, in the last section, we extend the concept of the Toeplitz operator to the bicomplex space, thus offering broader prospects.